(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The world is changing before our eyes. Digital technologies are gradually becoming an integral part of every area of daily life. It has been difficult to imagine the past years with the help of electronics, computers, networks and many other important automated technologies in all areas. The term "digital economy" is used a lot today. Indeed, in many developed countries, the digital economy has had a significant impact on their development. The digital economy plays an important role in the life of society, in communication in education, from purchasing to manufacturing, and all parts of the economy have changed to the digital environment.